HUMAN RESOURCE CAPACITY DEVELOPMENT OF BUREAUCRATS WITHIN THE LOCAL GOVERNMENT OF EAST BARITO REGENCY, INDONESIA - Indra Gunawan; Fernandes Simangunsong; Rizari; Andi Masrich (Jurnal Ilmiah Wahana Bhakti Praja, 2025)
The present study commences with the findings of the phenomenon of the problem of the low capacity of bureaucratic human resources, especially in public services in the Regional Government of East Barito Regency. The district's public service compliance rating is the lowest in Central Kalimantan Province. This study aims to reveal data related to the development of bureaucrats' human resource capacity in the Local Government. The analytical framework employed in this study draws upon the integrated quality management theory of W. Edwards Deming, encompassing the following aspects: (1) Plan, (2) Do, (3) Check or study, and (4) Act. A descriptive qualitative method was employed in this research. The data collection process involved a combination of interview techniques, observational studies, and document analysis, with the researchers themselves serving as the instruments for data collection. The data sources for this research include regional leaders, leaders of related OPDs, several bureaucratic staff members, and the Chairman of the DPRD. To ensure the reliability of the findings, a triangulation approach was employed, involving the synthesis of data from multiple sources and collection techniques. The results indicated that the enhancement of bureaucrats' human resource capacity within the East Barito Regency Regional Government has been effectively executed and is aligned with the stages of integrated quality management as proposed by Edwards Deming, thereby ensuring the effective and efficient achievement of objectives.